Discovering future research trends of journalism studies in Southeast Asia: comparison between Indonesia and Malaysia using bibliometric approach - Dadang Rahmat Hidayat,; Hanny Hafiar,; Kholidil Amin, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Contemporary communication technology developments influence trends in global journalism studies. Global journalism trends studies have also affected journalism studies across Southeast Asian countries, such as Indonesia and Malaysia. Journalism studies in both countries are inseparable from the culture of journalism and related research. The culture of journalism and research is associated with social, political, and academic dynamics, which have prompted significant changes in recent times. Indonesia and Malaysia are geographically and culturally close countries, exhibiting strategic positions in Southeast Asia. The current research aims to discover the trends in journalism studies in Indonesia and Malaysia and their comparisons. The present study employed the bibliometric method, and the data were retrieved from Web of Science Core Collection (WoS) using VOSviewer. The results suggested several similarities and differences between the two countries' documents, hinting at future trends in journalism studies in both countries. The topic trends and research collaborations are also discussed in this paper. The present study provides an overview of future trends in journalism studies in Indonesia and Malaysia based on data from their journalism studies over the last twelve years. Concerning keyword mapping, research publications on Indonesian and Malaysian journalism studies feature a tendency to link the existence of the Internet, social, political, and religious conditions with journalism culture and press freedom.